Phytochemical Screening and Total Flavonoid Content of Annona squamosa and Centella asiatica Ethanolic Extracts for Diabetic Wound Patch - Junaedi Junaedi; Yetri Elisya; Ulya Syafrina (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Diabetic wounds are one of the chronic complications of diabetes mellitus, characterized by delayed healing and a high risk of bacterial infection. The development of natural product-based pharmaceutical preparations is considered a promising alternative approach due to their relative safety and wide availability. Soursop leaves (Annona squamosa L.) and gotu kola leaves (Centella asiatica L.) are known to contain various secondary metabolites that contribute to antibacterial activity and wound healing. This study aimed to perform phytochemical screening and determine the total flavonoid content of ethanolic extracts of soursop leaves and gotu kola leaves as a scientific basis for the development of an antibacterial patch for diabetic wound management. Extraction was conducted using maceration with 96% ethanol. Qualitative phytochemical screening was performed to identify flavonoids, phenolics, tannins, saponins, steroids, and alkaloids. Total flavonoid content was determined using UV–Vis spectrophotometry with quercetin as the reference standard at a maximum wavelength of 427 nm. The results showed that the extraction yields of soursop leaf and gotu kola leaf ethanolic extracts were 14.64% and 14.72%, respectively. Both extracts contained flavonoids, phenolics, tannins, steroids, and alkaloids, while saponins were detected only in the gotu kola leaf extract. The total flavonoid contents of soursop leaf and gotu kola leaf extracts were 1.5% and 1.12%, respectively. In conclusion, ethanolic extracts of soursop leaves and gotu kola leaves possess phytochemical profiles that support antibacterial and wound-healing activities, indicating their potential as active ingredients in antibacterial patch formulations for diabetic wounds.